Alterations in resting‐state global brain connectivity in bipolar I disorder patients with prior suicide attempt. (11th October 2020) - Cheng, Xiaofang; Chen, Jianshan; Zhang, Xiaofei; Zhang, Yihe; Wu, Qiuxia; Ma, Qing; Sun, Jiaqi; Zou, Wenjin; Lin, Taifeng; Zhong, Liangda; Deng, Wenhao; Sun, Xiaoyi; et al.
Abstract: Background: Bipolar I disorder (BD‐I) is associated with a high risk of suicide attempt; however, the neural circuit dysfunction that confers suicidal vulnerability in individuals with this disorder remains largely unknown. Resting‐state functional magnetic resonance imaging (rs‐fMRI) allows non‐invasive mapping of brain functional connectivity. The current study used an unbiased voxel‐based graph theory analysis of rs‐fMRI to investigate the intrinsic brain networks of BD‐I patients with and without suicide attempt. Methods: A total of 30 BD‐I patients with suicide attempt (attempter group), 82 patients without suicide attempt (non‐attempter group), and 67 healthy controls underwent rs‐fMRI scan, and then global brain connectivity (GBC) was computed as the sum of connections of each voxel with all other gray matter voxels in the brain. Results: Compared with the non‐attempter group, we found regional differences in GBC values in emotion‐encoding circuits, including the left superior temporal gyrus, bilateral insula/rolandic operculum, and right precuneus (PCu)/cuneus in the bipolar disorder (BD) attempter group, and these disrupted hub‐like regions displayed fair to good power in distinguishing attempters from non‐attempters among BD‐I patients. GBC values of the right PCu/cuneus were positively correlated with illness duration and education in the attempter group. Conclusions: Our results indicate that abnormal connectivity patterns in emotion‐encoding circuits are associated with the increasing risk of vulnerability to suicide attempt in BD patients, and global dysconnectivity across these emotion‐encoding circuits might serve as potential biomarkers for classification of suicide attempt in BD patients.